Pelatihan Kepemimpinan Transformasional Calon Guru: Konsep, Integrasi, dan Evaluasinya dalam Pembelajaran - Blegur, Jusuf; Ena, Zet; Tlonaen, Zuvyati Aryani; Erny S. N. Hambandima (LPPM Universitas HKBP Nommensen, 2024)
This community service aims to increase students' knowledge and transformational leadership skills so that they can apply transformational leadership when carrying out learning practices in the classroom in the future. Nineteen students participated in the activity, but only 18 completed the evaluation. The science and technology transfer team includes the concepts and dimensions of transformational leadership, integration strategies for transformational leadership using scientific learning models, and how to evaluate students' transformational leadership. The three sciences and technologies were transferred using three methods, namely lectures and discussions, exercises, as well as presentations and reflections. The team evaluated service activities (pre test-post test) using seven open questions developed from the dimensions of transformational leadership developed by Carless et al. (2000). The results showed an average increase in understanding of transformational leadership in the medium category (0.3 <0.7). The highest increase was in the second dimension, namely team development, with a value of 0.70. Meanwhile, the dimension with the lowest increase was charismatic, with a value of 0.30. The other five dimensions are in the value range of 0.47-0.65 or are included in the medium category. In the future, service can be expanded by evaluating students' transformational leadership from the perspective of team/group members in learning activities to provide a more operational evaluation perspective on students' transformational leadership experiences.